S. Zoreh Kermani, Pagan Family Values: Childhood and the Religious Imagination in Contemporary American Paganism (New York: New York University Press, 2013), 250 pp., $27 (pbk), ISBN: 978-1-4798-9460-4 - Versteeg, Peter Gerrit Albert (Journal for the study of religion, nature and culture, 2017)
S. Zoreh Kermani, Pagan Family Values: Childhood and the Religious Imagination inContemporary American Paganism (New York: New York University Press, 2013), 250pp., $27 (pbk), ISBN: 978-1-4798-9460-4